Effectiveness of Non-Performing Loans Management at the Penglatan Traditional Village Credit Institution (LPD) - I Ketut Suardika; Mertyani Sari Dewi (Universitas Pendidikan Ganesha, 2021)
As a microfinance institution, the LPD, which is finance belonging to the village of Pakraman, aims to collect funds from the community to be further channeled back to the community. Seeing the critical role of the LPD as a micro institution in Bali, the LPD institution with traditional villages, and the government's desire to develop LPD in Bali, the existence of the LPD needs to be maintained and maintained. This study aims to determine the effectiveness of managing Non Performing Loans (NPL) in LPd Desa Adat Penglatan through the Non-Performing Loan Ratio (NPL), Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Earning Asset Quality (KAP) and Costs. Operating Operating Income (BOPO). This research was conducted at the Village Credit Institution (LPD) of the Penglatan Traditional Village. The instrument used to collect data is a questionnaire. This study used a population and 36 months or three-year samples using the purposive sampling technique. The collection technique uses an observation process on financial statement data. The techniques used in analyzing the data are Multiple Linear Regression Analysis, Classical Assumption Test Analysis, F-Test Analysis (F-Test), Determination Analysis, and T-Test Analysis (T-Test). The results of this study explain that the Capital Adequacy Ratio (CAR) has a significant negative effect on Non Performing Loans (NPL) and Loan to Deposit Ratio (LDR), Earning Assets Quality (KAP), and Operating Income Operating Costs (BOPO) have a significant influence for Non-Performing Loans (NPL).